ROOT-GROWTH AND MINERAL-NUTRITION OF CORN HYBRIDS AS AFFECTED BY PHOSPHORUS AND LIME - Rosolem, Ciro Antonio [UNESP]; Assis, J. S.; Santiago, A. D. (Taylor & Francis Inc, 1994)
The effects of triple superphosphate (TS) and liming on macronutrient accumulation and root growth of Pioneer 3072 and Cargill 505 com hybrids were studied. Com plants were grown up to 30 days in pots with 7 L of a dark red Latosol sandy loam (Haplortox). Lime was applied to raise base saturation to 30, 50, and 70%, in two levels of phosphorus (P) fertilization with TS (0 and 200 ppm P). There was an increase in root surface due to lime only in pots without TS, with no effects on plant growth or nutrition. Both com hybrids responded to P fertilization, but Pioneer yielded more dry matter than Cargill. The roots of Cargill were thicker and, when in TS presence, were longer and had a larger surface than Pioneer. There was an increase in macronutrient uptake in the P fertilized pots. Pioneer required more nutrients and showed a higher efficiency in acquiring and utilizing the nutrients from the soil. A higher response of Pioneer in dry matter and nutrient acquisition was more related to the physiological efficiency than to root morphology.